Control climático, tectónico y eustático en depósitos del Carniense (Triásico Superior) del SE de la Península Ibérica - García Hidalgo, J.F.; Arche, A.; López Gómez, J. (Journal of Iberian Geology, 2002)
The Manuel Sandstone Formation or K2 from Ortí (1974) is a clastic intercalation in the middle of the Keuper facies of SE Spain. This formation corresponds to a low-stand systems tract (LST) and it can be subdivided into three minor cycles that can be traced all over the area here studied. Its age is late Cordevolian-early Julian (lower-middle Karnian) according to the palynomorphs that are found in several localities. A stratigraphical correlation of the formation from Alhambra (Ciudad Real) and Chiclana de Segura (Jaén) to Jaraco (Valencia) is shown, and the mutual influences of climate, tectonics and eustatism that controlled the lateral change from a classic Keuper facies from the E to a purely siliciclastic one to the Ware discussed.